The effect of ortho-substitution on the efficacy of biphenyls in mediating electron transfer from lithium - Donohoe, T; Kershaw, N; Baron, R; Compton, R (2009)
A systematic study into the effect of increasing ortho-substitution of a range of biphenyls with respect to their ability to mediate electron transfer from lithium metal is described. A synthetic investigation has demonstrated the requirements for effective mediation. The electrochemical reduction of the mediators and of the two substrates was studied in THF, 0.1 M TBAP, at platinum microelectrodes both at room temperature and at low temperature. The formal potentials, Ef0 extracted from the cyclic voltammograms, are in agreement with results of the synthetic study and computational calculations also provide a correlation. © 2009 Elsevier Ltd. All rights reserved.